Glossier : from beauty blog to billion-dollar brand community - Upton, Alexandra E.; O'Brien, Justin (London : SAGE Publications: SAGE Business Cases Originals, 2021)
Vogue trained Emily Weiss created a USD 1.2 billion valued social media beauty business from scratch, spun out from her side project blog Into the Gloss. Weiss spotted a clear gap in the market for a fully integrated beauty advice community for real, rather than idealized, women. The vertically integrated Glossier brand used data analytics and insight gleaned from community posts and feedback to provide a powerful understanding of its audience. This enabled the development of compelling and highly engaging advice content and the capability to effectively identify unsatisfied product formulation needs.A bottom up, customer centric launch strategy using sophisticated search engine optimization, a strong focus on user experience, and a distinctive communications style all helped to differentiate the new brand of Glossier from its better known and better financed competitors. Weiss recognized early on that her company needed to maintain her blog's original voice and brand identity whilst simultaneously scaling up to fund investment in leading digital marketing tech. Through the application of insightful user generated content strategies, the Glossier management team were able to cut costs, build awareness, and maintain their voice in an authentic way. But, as big brands wised up to community based social marketing techniques and large influencers eyed lucrative direct-to-consumer beauty product brand extensions, could Emily Weiss's Glossier continue to be a trailblazing success?This student-academic, co-created case study uses only publicly available information. It is designed to encourage marketing students to appreciate how innovative search engine optimization practice and a powerful direct-to-consumer business model was used to scale a passion blog into a unicorn beauty community, by leveraging user generated content and peer-to-peer recommendation.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Glossier; Advertising -- Cosmetics -- Case studies; Business planning -- Case studies